Framing the benefits of higher education participation from the perspective of non-completers - Cunninghame, Ian; Pitman, Tim (2019)
Ensuring that students of all backgrounds are smoothly transitioned through the stages of access, participation and completion in higher education has been the focus of much public policy and research in recent decades. Subsequently, public policy discourse treats those who do not complete their higher education degrees as unsuccessful, despite a lack of research considering the beneficial outcomes of non-completing students. Evidence of beneficial outcomes of higher education participation without completion has potential to challenge the deficit-centric discourse of completion dependent on a binary view of success and failure. This article details a critical discourse analysis of responses to a 2017 survey of university non-completers asked ‘were there any benefits from the time you spent doing an [sic] incomplete degree?’. This study finds that non-completers experience a wide range of benefits from incomplete studies despite the dominant discourse discounting their experiences as unsuccessful. Additionally, this study presents a critique of framing surveys of non-completing students within the normative bounds of success as completion in higher education, and instead calls for a more nuanced construction of success in higher education.